Humanization in Prophetic Leadership: The Role of AIK Lecturers in Fostering Religious Moderation in Muhammadiyah Higher Education - Ahmad Syaipul Bahri; Adlan Fauzi Lubis; Bunyamin Bunyamin (STAI Hubbulwathan Duri, 2026)
Intolerance and exclusivism continue to pose challenges in Indonesian higher education, underscoring the need for leadership models that promote inclusive and moderate religious attitudes. This study investigates the humanization dimension of prophetic leadership practiced by AIK (Al-Islam and Kemuhammadiyahan) lecturers at Universitas Teknologi Muhammadiyah Jakarta (UTMJ) in strengthening students’ religious moderation.A qualitative descriptive approach was employed, with data collected through in-depth interviews, observations, and document analysis. The data were analyzed thematically to identify patterns and core values embedded in lecturers’ leadership practices.The findings reveal five key values underpinning the humanization model of prophetic leadership: moral and academic role modeling, tolerance for diversity, compassion in mentoring, justice in assessment and interaction, and integrity in upholding Islamic and Muhammadiyah principles. These values are consistently integrated into teaching practices and social engagement, contributing to the development of students’ wasathiyyah (moderate religious attitudes).The study concludes that the humanization dimension of prophetic leadership functions as a transformative framework for fostering students’ moral character and promoting an inclusive, ethical academic culture. This model offers practical implications for strengthening religious moderation within Muhammadiyah higher education and potentially in broader academic contexts.